The 'Mighty Girl' Effect: Does Parenting Daughters Alter Attitudes towards Gender Roles? - Mireia Borrell-Porta; Joan Costa-Font; Julia Philipp (Institute of Labor Economics (IZA), 2018)
Understanding the malleability of gender norms is crucial to address gender inequalities. We study the effect of parenting daughters on a gender role attitude relating to the traditional male breadwinner model: whether the husband should earn and the wife stay at home. We control for other covariates that capture alternative explanations for gender role perceptions. Our results suggest evidence of a positive effect of parenting daughters on acceptance of less traditional gender roles. The effect is only robust among fathers and driven by parenting school age rather than younger daughters, which is consistent with a social identity explanation. Results suggest that parenting daughters of school age (as opposed to parenting only sons) increases the probability to disagree with the statement that 'husband should earn and wife stay at home' by over 5 percentage points. We conclude that gender role attitudes can be shaped by events that occur later in life.
Keywords: J7; Z1; 330; gender roles; attitudes to gender roles; maternal employment; attitude formation; daughters